Facial Attractiveness and Lifetime Earnings: Evidence from a Cohort Study - Scholz, John Karl; Sicinski, Kamil (The Review of Economics and Statistics, 2015)
We use unique longitudinal data to document an economically and statistically significant positive correlation between the facial attractiveness of male high school graduates and their subsequent labor market earnings. There are only weak links between facial attractiveness and direct measures of cognitive skills and no link between facial attractiveness and mortality. Even after including a lengthy set of characteristics, including IQ, high school activities, proxy measures for confidence and personality, family background, and additional respondent characteristics in an empirical model of earnings, the attractiveness premium is present in the respondents' mid-30s and early 50s. Our findings are consistent with attractiveness being an enduring, positive labor market characteristic.